Wireless-Sensor-Networks-based healthcare system: a survey on the view of communication paradigms. (6th September 2011) - Huo, Hongwei; Xu, Youzhi; Zhang, Hongke; Chuang, Yu Hsiu; Wu, Tzong-Chen
Wireless Sensor Networks (WSNs)-based technology has invaded the Medicine and Healthcare scopes. The potential to replace wired iatrical equipments with wireless ones in the hospital will change the whole healthcare system out of question. The objective of this paper is to survey the research on the WSN-based healthcare systems to enhance further understanding of this technology for users or engineers. In this paper, we outline the structure of the WSN-based healthcare system, analyse the design space, summarise and compare the states of some well-documented applications and discuss the key research points of these systems.